KEWIRAUSAHAN DALAM PENDIDIKAN ISLAM - Ficki Padli Pardede; Aldira Salsabilla; Andika Jun Priadi; Ananda Pane; Khalid Jamhuri Harahap; Sultoni; Fadhly Yassin Tanjung; Wardi; Mhd Dedi Hcomaludin Jamil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Entrepreneurship in Islam is not merely a profession, but a form of worship and muamalah that requires religious understanding to avoid fraudulent practices. This study aims to examine the concept, implementation, and impact of religious-based entrepreneurship education in shaping student independence. Using a qualitative method with a literature review and school-based case study approach, this research explores the integration of Islamic values into the formal and extracurricular curriculum of Islamic Religious Education (PAI). The results indicate that entrepreneurship education is crucial to implement from high school to higher education levels. Comprehensive and applicable PAI lessons significantly contribute to the internalization of honesty, trustworthiness, justice, and social responsibility. This process successfully stimulates students' interest in Sharia entrepreneurship and develops independence grounded in the Qur'an and the exemplary character of Prophet Muhammad SAW. The implication of this study emphasizes the urgency of integrating Islamic values to foster a generation of entrepreneurs who are both financially competent and morally upright.